Clothing as a factor in bullying cases in a selected private high school in Nueva Ecija - Dela Cruz, Ma. Deanne V. (College of Home Economics, University of the Philippines Diliman, 2014)
Abstract School bullying has become a national concern in the Philippines, following the implementation of the Anti-Bullying Act of 2012. Implicit in the phenomenon is the fact that not fitting in is a common reason for being a victim of bullying. However, little attention has been given to the involvement of clothing in bullying, considering that clothing is a universal symbol that represents belongingness and identification to a group. Thus, this research sought to find out if and how clothing becomes a factor in bullying cases in a selected school. It specifically aimed to determine specific reasons for bullying among high school students, determine if and how clothing ranks among the reasons for bullying, identify specific characteristics of clothing that serve as a motivation in bullying, and determine if bullying has an impact on the choice of clothes of the selected age group. A two-part survey was conducted in a private secondary school situated in a rural area. The study identified that the most common reasons for bullying were physical appearance, clothing style, and sexual orientation. Out of 90 participants drawn using convenience sampling technique, 67 or about 74% of the respondents confirmed that clothing style is a reason for bullying, ranking second after physical appearance. It supported the conclusion that dress was one of several variables affecting the acceptance or rejection in social groups. ?Not flattering? and ?not suitable for the occasion? were among the clothing characteristics that serve as motivation for clothing-related bullying incidents as well as being ?baduy?, ?jeje? and ?jologs?. However, the study showed that clothing-related bullying does not have any impact on the choice of clothes of the respondents. They do, however, admit being ?conscious? about the clothes they wear. The researcher recommends the use of probability sampling technique for fair representation of the population and interview or focus group discussion for more comprehensive responses.